Antioxidant activity of fermented coffee beans - Jelena, Jesslyn; Yustiantara, Putu Sanna (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
A green coffee bean contains phenolic compounds with strong antioxidant activity, such as chlorogenic acid. Fermentation is one of the ways to increase the antioxidant activity of coffee beans by using microorganisms. This review aims to study the antioxidant activity of fermented green coffee beans and the factors involved in the fermentation process. We selected original research articles providing data on the antioxidant activity of fermented green coffee beans published from 2015 to 2021. Fermented green coffee beans shows stronger antioxidant activity compared to the controls. The amount of substrate, yeast (as a starter), and fermentation duration influence the antioxidant activity of the fermented green coffee beans. The fermented green coffee beans with yeast had significantly higher antioxidant activity than those in unfermented coffee.